2021
DOI: 10.2147/ibpc.s285007
|View full text |Cite
|
Sign up to set email alerts
|

Are Community Health Center Patients Interested in Self-Measured Blood Pressure Monitoring (SMBP) – And Can They Do It?

Abstract: Introduction Self-measured blood pressure monitoring (SMBP) helps diagnose and manage hypertension from outside the clinic, which has implications for patient empowerment and outcomes, continuity of care, and resilience in care communities catering to vulnerable populations. Methods We instituted a protocol for SMBP among hypertensive patients at 9 community health centers in 3 states and administered questionnaires to patients before and after the protocol was institut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 24 publications
0
8
0
Order By: Relevance
“… 47 People with hypertension who self-monitor blood pressure felt more inclined to adopt lifestyle changes 48 and were confident in communicating their readings to clinicians. 49 However, other patients with hypertension felt confused about the utility of home blood pressure monitoring, particularly if they were not aware of how to interpret the results. 47 Previous work has also highlighted challenges including inaccuracy in self-monitoring blood pressure, 50 patients being unaware about targets, 49 or lack of training from clinicians.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 47 People with hypertension who self-monitor blood pressure felt more inclined to adopt lifestyle changes 48 and were confident in communicating their readings to clinicians. 49 However, other patients with hypertension felt confused about the utility of home blood pressure monitoring, particularly if they were not aware of how to interpret the results. 47 Previous work has also highlighted challenges including inaccuracy in self-monitoring blood pressure, 50 patients being unaware about targets, 49 or lack of training from clinicians.…”
Section: Discussionmentioning
confidence: 99%
“… 49 However, other patients with hypertension felt confused about the utility of home blood pressure monitoring, particularly if they were not aware of how to interpret the results. 47 Previous work has also highlighted challenges including inaccuracy in self-monitoring blood pressure, 50 patients being unaware about targets, 49 or lack of training from clinicians. 51 Our synthesis suggests that patients were more engaged and had a sense of achievement in taking control of their care, and felt reassured in being able to monitor blood pressure at home between clinical appointments.…”
Section: Discussionmentioning
confidence: 99%
“…So that the application of home telemonitoring to monitor and measure blood pressure during a pandemic is very potential (Tim APJII, 2021). In addition to the purpose of monitoring blood pressure, self-monitoring blood pressure can be an early detection tool for hypertension in the community (Roy et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…It is necessary to conduct training and education related to the use of blood pressure detection devices as an important instrument in implementing telemonitoring blood pressure at home (Roy et al, 2021). The study conducted by Ringrose et al (2017) found that the blood pressure measurement tools owned by many patients were inaccurate to more than or equal to 5 mmHg.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation